Halal Assurance Development Strategy In Indonesia - Adriani, Adriani; Siradjuddin, Siradjuddin; Mukhtar Lutfi; Nurlaela, Nurlaela (CV. Ulil Albab Corp, 2025)
This study uses a qualitative research method that provides an understanding of the strategy for developing halal assurance in Indonesia. This research method uses a literature review taken from several readings that discuss the existence of strategies, development and halal assurance. The results of this study are that halal products are rahmatan lil alamin for all people, especially for those who consume them and the business actors involved. In the development of the halal product industry, the implementation of sustainable policies that are in accordance with Islamic law will be oriented towards fair business and be able to create a just and prosperous society. In this case, the emphasis of the strategy is carried out by prioritizing the development of aspects of the domestic halal product industry and creating a business network in the global market that will grow the Indonesian halal product industry to dominate the global market. This is expected to increase the effectiveness, efficiency, and sustainability in the development of the halal product industry and make development rational and on target. Therefore, community involvement in the process of developing the halal product industry is very important in order to optimize existing resources and create a good communication climate between the government and the community